Paraprofessionals' Perceived Skills and Needs in Supporting Students With Autism Spectrum Disorder. (December 2022) - Coogle, Christan Grygas; Walker, Virginia L.; Ottley, Jennifer; Allan, Darcey; Irwin, Daniel
There is a research-to-practice gap in the identification and use of evidence-based practices in special education. One way to better understand the persistent gap between research and practice and to inform professional development efforts is through gaining an understanding of teacher and paraprofessional perceptions. We conducted a survey study to identify paraprofessionals' perceived skills and needs regarding categories of practices aligning with evidence-based practices for students with autism spectrum disorder. A total of 768 paraprofessionals completed the survey. We used descriptive statistics, one-way analyses of variance (ANOVAs), post hoc analyses, and chi-square tests to analyze paraprofessionals' responses. Paraprofessionals reported a range of responses and several of their responses differed significantly in relation to their experience and the population of students they supported. Findings suggest there is a need to individualize professional development based on both classroom and paraprofessional training needs. Future research is needed to determine how paraprofessionals' perceptions align with their practice.